DOCUMENTATION ON THE GREEKS IN CANADA. ARCHIVES OF THE CENTRE FOR HELLENIC STUDIES AND RESEARCH CANADA-KEEK - –, – (Études helléniques / Hellenic Studies, 2002)
Passport given by the Italian Consulate of Montreal (Quebec-Canada) to Emmanuel Georgoulis a Greek immigrant from Dodeconese islands, at that time occupied by Italy, dated May 31, 1932. Apparently Georgoulis entered Canada in 1928 (From the book of Vissarionas Hatzidavid, Greek Dodecanesians in Montreal which will soon be published by the Centre of Hellenic Studies and Research Canada-KEEK).